ANALISIS PERAN PEMBIAYAAN BANK SYARIAH TERHADAP PRODUKTIVITAS MASYARAKAT DI ERA DIGITAL - Sopiyanti, Vina; Fasa, Muhammad Iqbal; Suharto, Suharto (I-Economics, 2021)
This study examines the role of Islamic bank financing on community productivity. This study observes that Islamic bank financing has a more significant influence on company growth. Stakeholders such as managers and investors are expected to change their views on Islamic bank financing, which is currently seen as part of a religious practice. This can lead to the use of Islamic bank financing by companies.[1] Islamic banks can play a role in improving people's welfare. Through the intermediation function, Islamic banks can collect funds and channel them back to the community in the form of financing for productive purposes. The purpose of this study is to determine the relationship between Islamic bank financing and community productivity in the digital age and the impact of Islamic bank financing on the Indonesian economy in the digital age. This study uses descriptive qualitative and literature study through the readings of previous researchers. The results of this study reveal that Islamic bank financing plays a role in increasing economic activity and employment. Islamic bank financing provides a positive role to improve economic activities in each sector.